The feasibility of using natural rice husk ash in structural concrete. Part I: mechanical properties and microstructure - Isaia, Geraldo Cechella (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2010)
Rice husk needs to be burnt at controlled temperatures and be ground to increase its pozzolanic reactivity, in order to be used in structural concrete. This article examines the use of natural and residual rice husk ash (RHA) burnt without temperature control and without grinding, aiming to simplify the processing of rice husk ash and increase its use in conventional concretes, closed to the location where RHA is produced. This study investigated the order in which materials are added to the mixture and at mixing times so as to obtain better self-grinding performance inside of the drum. Reference concrete mixtures with Portland cement and with 15% and 25% cement mass replacement by natural and ground RHA were tested. The following tests were performed: axial compression strength, tensile strength by diametral compression, elasticity modulus determination, total shrinkage, mercury intrusion porosimetry, chemically combined water and SEM. The analysis of the results indicates the feasibility of replacing 15% cement by natural RHA, without significant loss of tensile strength and elasticity modulus at 28 days, with total recovery at 91 days for concretes with compression strength between 25 and 40 MPa.